EXPLORING CULTURAL CHALLENGES IN ENGLISH-UZBEK TRANSLATION: A NEW APPROACH TO DEVELOPING TRANSLATOR ASSESSMENT. (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation: This article investigates cultural challenges in English-Uzbek translation and introduces a new approach to developing translator assessment criteria. By analyzing linguistic, cultural, and contextual barriers, the research proposes innovative strategies for evaluating translators' competence. The study integrates insights from translation theory, linguistic anthropology, and cross-cultural communication, offering a practical framework for improving translator training and evaluation.